The Shadows of Liberation: Creating Hope and Meaning in Creative Self-Study Inquiry - Sawyer, Richard D. (Adult Education Discourses, 2023)
In this essay, the author intends to examine how his experience isolating at home during the COVID-19 pandemic unfolded as a generative self-study experience. After a chance discovery of old photos and artifacts from his teenage years, he began a currere (a self-study of educational and curricular associations) from when he was a high school (secondary) student. In this currere he reconstituted more than remembered the past, emphasizing free association in the four stages (regressive, progressive, analytic, synthetic) of currere. In the study he exposes the distortion of his memories in relation to dominant (and marginalizing) normative discourses and discusses their erasure. In this process he tells how he experienced an epiphany in the recovery of a youthful narrative of joy, hope, and resistance. This initial study, in which the author emphasized the value of subjectivity, laid the foundation for additional projects examining the role of subjectivity more broadly in academic studies. These projects included an edited book on Applied Linguistics and a special journal issue on the topic of curricular epistemicide and erasure.